PROFIL AROMA DAN MUTU SENSORI CITARASA PASTA KAKAO UNGGULAN DARI BEBERAPA DAERAH DI INDONESIA [Aroma and Flavor Sensory Profiles of Superior Cocoa Liquors from Different Regions in Indonesia] - Intan Kusumaningrum; C. Hanny Wijaya; Feri Kusnandar; - Misnawi; Ariza Budi Tunjung Sari (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2014)
PROFIL AROMA DAN MUTU SENSORI CITARASA PASTA KAKAO UNGGULANDARI BEBERAPA DAERAH DI INDONESIA[Aroma and Flavor Sensory Profiles of Superior Cocoa Liquors from Different Regions in Indonesia]Intan Kusumaningrum1)*, C. Hanny Wijaya2), Feri Kusnandar 2), Misnawi3) dan Ariza Budi Tunjung Sari3)1) Program Studi Magister Ilmu Pangan, Institut Pertanian Bogor, Bogor2) Departemen Ilmu dan Teknologi Pangan, Fakultas Teknologi Pertanian, Institut Pertanian Bogor, Bogor3) Pusat Penelitian Kopi dan Kakao Indonesia, Jember Diterima 12 Desember 2013 / Disetujui 06 Mei 2014ABSTRACT The objective of this research was to compare the aroma profiles and flavor sensory qualities of three cocoa liquors obtained from different regions in Indonesia, namely East Java, South Sulawesi and Bali. The Ghanaian cocoa liquor was used as the reference. The aroma of cocoa liquors was extracted by using a Solid Phase Microextraction (SPME), followed by detection with Gas Chromatography-Mass Spectrometry/Olfactometry (GC-MS/O) with the Nassal Impact Frequency (NIF) method. A total of 28 aroma active compounds in the cocoa liquors were identified, where in 21, 19, 22 and 18 compounds were detected in East Java, Bali, South Sulawesi and Ghana liquors, respectively. The profiles of these three liquors were not only different from one another but were also different from the reference. East Java liquor had a specific aroma of strong chocolate, enriched with creamy, caramel and coffee bean aroma, whileBali liquor was dominated by creamy, caramel and sweet, and South Sulawesi liquor was specified by its sweet green aroma. The aroma sensory characteristic was evaluated by descriptive test, presenting the aroma of nutty, acid, caramel, earthy and chocolate, while the taste sensory attributes included astringency, bitterness and acidity. The sensory profile analysis was carried out by applying a Quantitative Descriptive Analysis (QDA) method. Accompired with preference and ranking tests were also conducted. Among the three cocoa liquors, the sensory profile of South Sulawesi was the most similar to that of Ghanaian cocoa liquor. However, the cocoa liquor from Bali and East Java cocoa were more preferred comparing to the liquor from South Sulawesi.